(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of communicator credibility including expertise, trustworthiness, and attractiveness on the behavior of practicing Ahlussunnah wal Jama’ah An-Nahdliyah (Aswaja) values ​​among participants of the IPNU-IPPNU Member Loyalty Period (MAKESTA) training in Bekasi Regency. This study uses an explanatory quantitative approach with a survey method, data were collected from the entire population of 63 members who had participated in MAKESTA in 2025 through a Likert scale questionnaire 1–4 that had been tested for validity and reliability. Data analysis was carried out using simple linear regression and partial t-test. The results showed that communicator expertise had no significant effect (t = 1.101; p = 0.275), while trustworthiness (t = 3.585; p = 0.000) and communicator attractiveness (t = 3.682; p = 0.001) had a significant effect on the behavior of practicing Aswaja values. Simultaneously, these three dimensions were able to explain 76.6% of the variance in practice behavior (R² = 0.766). This finding strengthens the theory of source credibility by revealing that in the context of religious values ​​education, the affective dimension (trustworthiness and attractiveness) is more dominant than the cognitive dimension (expertise). The implication is that the selection and development of material for religious organization cadres needs to prioritize aspects of personal integrity and communicator attractiveness.